The Influence of Heat-Killed Enterococcus faecium BGPAS1-3 on the Tight Junction Protein Expression and Immune Function in Differentiated Caco-2 Cells Infected With Listeria monocytogenes ATCC 19111 - Popović, Nikola; Djokić, Jelena; Brdarić, Emilija; Dinić, Miroslav; Terzić-Vidojević, Amarela; Golić, Nataša; Veljović, Katarina (Frontiers in Microbiology, 2019)
Listeria monocytogenes, the common foodborne pathogenic bacteria, compromise the intestinal epithelial barrier, which leads to development of the listeriosis, very serious disease especially among immunocompromised individuals. L. monocytogenes infection usually requires antibiotic treatment, but excessive use of antibiotics is closely related to the emergence of antibiotic resistance and the destruction of gut microbiota. Probiotics, including lactic acid bacteria, have been repeatedly proven as an alternative approach for the treatment of various infections. In that mean, we have analyzed the potential of Enterococcus faecium BGPAS1-3, a dairy isolate, with strong direct antilisterial effect, to modulate the response of differentiated Caco-2, intestinal epithelial cells, on L. monocytogenes ATCC 19111 infection. Considering the controversial status of enterococci, we additionally tested the antilisterial potential of heat-killed BGPAS1-3. Importantly, we showed that the molecule with antilisterial effect is protein in the bacterial cell wall highly resistant to the high-temperature treatment. Additionally, heat-killed BGPAS1-3 could prevent tight junction disruption in differentiated Caco-2 monolayer infected with L. monocytogenes ATCC 19111, simultaneously allowing the induction of immune mechanisms important for antilisterial host response and stimulates the production of protective TGF-β in intestinal epithelial cells. Finally, we showed that the modulation of MyD88 dependent TLR2 and TLR4 pathways by BGPAS1-3 are involved in host response against L. monocytogenes ATCC 19111. Considering that heat-killed BGPAS1-3 possess strong antilisterial effects, such postbiotic could be used as a more controllable and safer therapeutic.